Analysis of the Difficulty of Solving Physics Problems During Online Learning at SMA Negeri 1 Tikep Against the Online Media Used - Jahiruddin Jahiruddin (Research Collaboration Community (RCC), 2021)
Online learning is an alternative in the implementation of education in Indonesia. During the Covid-19 pandemic, education needs to be carried out, because education has an important role in the progress of a nation. Therefore, this study aims to analyze the difficulty of solving physics problems during online learning using online media at SMA Negeri 1 Tikep. The data used in this study were primary data obtained from questionnaires, and interviews with students of class X IPA 1. The location of this study was at SMAN 1 Tikep, in West Muna Regency, Southeast Sulawesi Province. This study uses a quantitative method approach in analyzing the difficulty of solving physics problems during online learning using online media. Based on the results obtained, only 29% of students can participate in online learning, while 71% of students cannot understand the material provided online. In addition, the level of students' ability to understand physics equations is 25, and the level of students' ability to solve problems from physics equations is very low, namely 18%. Based on the results of the study, it can be said that online physics learning has not run optimally. This is influenced by the supporting facilities for the implementation of online learning are not supported, such as the quality of the internet network is good. In addition, the use of the WhatsApp application which has limited features is a problem in online learning. So that the online physics learning that is carried out is not effective, which has an impact on students who are unable to understand and solve physics equations. Based on the results of the study, it is hoped that it can be used as an evaluation material for the government in providing supporting facilities for the implementation of online learning.